Microevolution of Pieris butterfly genes involved in host plant adaptation along a host plant community cline. Issue 11 (18th April 2022) - Okamura, Yu; Sato, Ai; Kawaguchi, Lina; Nagano, Atsushi J.; Murakami, Masashi; Vogel, Heiko; Kroymann, Juergen
Abstract: Herbivorous insects have evolved counteradaptations to overcome the chemical defences of their host plants. Several of these counteradaptations have been elucidated at the molecular level, in particular for insects specialized on cruciferous host plants. While the importance of these counteradaptations for host plant colonization is well established, little is known about their microevolutionary dynamics in the field. In particular, it is not known whether and how host plant diversity shapes diversity in insect counteradaptations. In this study, we examine patterns of host plant use and insect counteradaptation in three Pieris butterfly species across Japan. The larvae of these butterflies express nitrile‐specifier protein (NSP) and its paralogue major allergen (MA) in their gut to overcome the highly diversified glucosinolate–myrosinase defence system of their cruciferous host plants. Pieris napi and Pieris melete colonize wild Brassicaceae whereas Pieris rapae typically uses cultivated Brassica as a host, regardless of the local composition of wild crucifers. As expected, NSP and MA diversity was independent of the local composition of wild Brassicaceae in P. rapae . In contrast, NSP diversity correlated with local host plant diversity in both species that preferred wild Brassicaceae. Both P. melete and P. napi revealed two distinct major NSP alleles, which shaped diversity among local populations, albeit with different evolutionary trajectories. In comparison, MA showed no indication for local adaptation. Altogether, MA appeared to be evolutionary more conserved than NSP, suggesting that both genes play different roles in diverting host plant chemical defence.